The Use of Foreign Currency Derivatives and Firm Market Value - Allayannis, George; Weston, James P. (Review of Financial Studies, 2001)
This article examines the use of foreign currency derivatives (FCDs) in a sample of 720 large U.S. nonfinancial firms between 1990 and 1995 and its potential impact on firm value. Using Tobin’s Q as a proxy for firm value, we find a positive relation between firm value and the use of FCDs. The hedging premium is statistically and economically significant for firms with exposure to exchange rates and is on average 4.87% of firm value. We also find some evidence consistent with the hypothesis that hedging causes an increase in firm value.